Growth and relationship of phenotypic characteristics with gonadal pathology and tumour risk in patients with 45, X/46, XY mosaicism. (17th February 2021) - Poyrazoglu, Sukran; Bas, Firdevs; Karaman, Birsen; Yildiz, Melek; Basaran, Seher; Darendeliler, Feyza
Abstract: Objective: To evaluate the growth data, gonadal functions and tumour risk in children with 45, X/46, XY mosaicism. Design: We reviewed retrospectively the records of 45 patients with 45, X/46, XY mosaicism or variants presented to our Unit from 1989 to 2019. Results: The age at diagnosis ranged from 0.03 to 17.5 years. Twenty‐eight patients had genital anomaly, 14 patients had female external genitalia and 3 patients had normal male genitalia. Patients showed normal height under 2 years of age. Mean height standard deviation score (HSDS) of 19 patients diagnosed before 2 years of age was −0.9 ± 0.6 and that of 26 patients diagnosed after 2 years of age was −2.6 ± 1.5. Ten patients diagnosed before 2 years of age showed growth deceleration after 2 years of age (HSDS decreasing from −0.6 ± 0.7 to −1.4 ± 0.9). Twenty‐one patients reached adult height (AH). Growth hormone (GH) treatment was initiated in 10 patients. Although AHSDS of GH‐treated patients was significantly greater than their mean HSDS before GH therapy ( p  =.013), it was not significantly different from AHSDS of the untreated group. Seventeen (37.8%) patients exhibited phenotypical features of Turner syndrome (TS) other than short stature. Two patients with genital anomaly had gonadoblastoma and germ cell neoplasia in situ, and one patient with female external genitalia had gonadoblastoma. Conclusions: GH therapy seems to improve AH of patients. Both patients with genital anomaly and female external genitalia have increased risk of germ cell tumours.